IDDF2019-ABS-0139 Evaluation of narrow band imaging findings in microscopic colitis and targeted biopsies. (June 2019) - Bellam, Balaji; Shukla, Siddharth; Kochhar, Rakseh; Singh, Anupam Kumar; Rana, Satyavathi; Prasad, Kaushal K; Dhaka, Narender; Malik, Sarthak; Berry, Neha; Sharma, Megha; Sinha, Saroj Kant
Abstract : Background: Microscopic colitis (MC) is the cause of chronic diarrhoea which is often missed. Histopathology is a gold standard for diagnosis but colonic biopsy has a variable yield in view of normal endoscopy. We evaluated ileocolonic mucosa in suspected MC cases with narrow band imaging (NBI)and described its findings with outcome of targeted biopsy Methods: 53 adults with chronic diarrhea suspected to have MC were recruited after excluding malignancy, celiac disease, small intestinal bacterial overgrowth and inflammatory bowel disease. Routine blood tests, necessary imaging, stool analysis were done . Colonoscopy was done in all with ileal intubation if possible. HDWLE (high definition white light examination) and NBI finding were recorded . Routine biopsies on white light and targeted biopsies on NBI were taken and analysed by an expert gastrointestinal histopathologist as per statements of the European Microscopic Colitis Group 2012 Results: 43 patients were diagnosed to have MC [mean age - 45.83(±15.92), males - 27]. The WLE revealed normal mucosa in all patients. NBI showed type 1 pit pattern and regular vascular pattern in all patients with MC. Mucosal pattern was honey comb type in all. Focal areas of abnormal vascularity with focally obscure pit pattern was noted more frequently in cases than controls {81% vs 12.5% (p = 0.052)}. Histologically 25(58.1%) had collagenous colitis (CC), 14 (32.5%) had lymphocytic colitis (LC). Four patients (9.4%) had a mixed picture. The yield of WLE and NBI targeted biopsies was the same (p>0.05) Conclusions: Colonoscopic NBI findings in MC revealed a hitherto unreported and distinct focal areas of abnormal vascularity with focally obscure pit pattern. There was no significant difference in yield of NBI vs WLE biopsies